2016
DOI: 10.1016/j.anbehav.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

How practice makes perfect: the role of persistence, flexibility and learning in problem-solving efficiency

Abstract: To fully understand how problem solving ability provides adaptive advantages for animals, we should understand the mechanisms that support this ability. Recent studies have highlighted several behavioural traits including persistence, behavioural variety and behavioural/cognitive flexibility that contribute to problem solving success. However, any increment in these traits will increase time and energy costs in natural conditions, so they are not necessarily advantageous. To examine how behavioural traits vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 41 publications
(48 reference statements)
5
92
3
1
Order By: Relevance
“…Behavioral flexibility, Aesop's Fable, color discrimination, reversal learning, problem solving, Icteridae BACKGROUND Behavioral flexibility, defined here as the ability to change preferences when circumstances change based on learning from previous experience or using causal knowledge, is frequently implicated as a key factor involved in problem solving success and adapting behavior to changing environments (e.g., Lefebvre et al 1997, Griffin & Guez 2014, Buckner 2015, Chow et al 2016. Those individuals or species that are more behaviorally flexible are predicted to learn faster and better, and rely on more learning strategies to solve problems (Griffin & Guez 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral flexibility, Aesop's Fable, color discrimination, reversal learning, problem solving, Icteridae BACKGROUND Behavioral flexibility, defined here as the ability to change preferences when circumstances change based on learning from previous experience or using causal knowledge, is frequently implicated as a key factor involved in problem solving success and adapting behavior to changing environments (e.g., Lefebvre et al 1997, Griffin & Guez 2014, Buckner 2015, Chow et al 2016. Those individuals or species that are more behaviorally flexible are predicted to learn faster and better, and rely on more learning strategies to solve problems (Griffin & Guez 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The puzzle situation that inspired this model has been used in a series of experiments on problem-solving in squirrels (Chow, Lea, & Leaver 2016;Chow et al, 2017;Chow, Lurz, & Lea 2018;Chow et al, 2019). The basic design is fully described by Chow et al (2016), though later experiments involved some variations. It consists of a transparent, roughly cubical box supported on short legs above a solid pyramidal base.…”
Section: The Situation To Be Modeledmentioning
confidence: 99%
“…a i represents the preparedness of response i: the higher a i , the easier it is to learn that response (for the given Fig. 1 (a) Simplified diagram (not to scale) of the apparatus used by Chow et al (2016). In practice there were ten levers, five of which were baited with nuts and five were unbaited.…”
Section: Basic Principles Of the Model And Their Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…A successful trial was defined as any performance of the skill that demonstrated the focus SC; a successfult trial was defined as any skill attempt that met the focus SC for that week. Recent research (Chow, Lea, & Leaver, 2016) suggests that learning can be influenced by the number of trials completed, and success in those trials provides opportunities for greater benefit. Often, practice trials are a controlled variable in research to understand the differences between other influences (Corrêa, Walter, Torriani-Pasin, Barros, & Tani, 2014).…”
Section: Test Of Gross Motor Development-3 Rd Edition (Tgmd-3)mentioning
confidence: 99%